Exploitation, Resettlement, Mass Murder : Political and Economic Planning for German Occupation Policy in the Soviet Union, 1940-1941. - Kay, Alex J. (War and genocide., 2013)
Convinced before the onset of Operation ""Barbarossa"" in June 1941 of both the ease, with which the Red Army would be defeated and the likelihood that the Soviet Union would collapse, the Nazi regime envisaged a radical and far-reaching occupation policy which would result in the political, economic and racial reorganization of the occupied Soviet territories and bring about the deaths of 'x million people' through a conscious policy of starvation. This study traces the step-by-step development of high-level planning for the occupation policy in the Soviet territories over a twelve-month per